Racism in Lee Daniels' Movie The Butler (Lembaga Pengembangan Kinerja Dosen, 2022)
The Butler movie explored discrimination between white and black people that created social grade which lead to the conflict. This became a very interesting one to explore. The purpose of this study was to find more about the racism in such movie. The researcher used a qualitative descriptive method, and the research material was a dialogue from the movie